Sex determination in mammalian germ cells: extrinsic versus intrinsic factors - Bowles, Josephine; Koopman, Peter (Reproduction (Cambridge, England), 2010)
Mammalian germ cells do not determine their sexual fate based on their XX or XY chromosomal constitution. Instead, sexual fate is dependent on the gonadal environment in which they develop. In a fetal testis, germ cells commit to the spermatogenic programme of development during fetal life, although they do not enter meiosis until puberty. In a fetal ovary, germ cells commit to oogenesis by entering prophase of meiosis I. Although it was believed previously that germ cells are pre-programmed to enter meiosis unless they are actively prevented from doing so, recent results indicate that meiosis is triggered by a signaling molecule, retinoic acid (RA). Meiosis is avoided in the fetal testis because a male-specifically expressed enzyme actively degrades RA during the critical time period. Additional extrinsic factors are likely to influence sexual fate of the germ cells, and in particular, we postulate that an additional male-specific fate-determining factor or factors is involved. The full complement of intrinsic factors that underlie the competence of gonadal germ cells to respond to RA and other extrinsic factors is yet to be defined.